Lexicography and linguistic human rights: codifying continua in Scotland and African America - Scott, M (2010)
In recent years there has been much debate over the status of varieties of language that have a close relationship to English, and although sociologists have long argued that such language varieties should be respected and valued, their words have often been ignored by the decision makers responsible for government and education policy. Furthermore, sociolinguistic ideas are not often successfully communicated to the general public, with the result that 'minority' varieties of language (and their speakers) are often marginalised. This is clearly demonstrated by such events as the Oakland School Controversy (in the case of African American) and by the protracted debates over the recognition of Scots as the language variety used by many Scottish children. This paper focuses on the role of dictionary-makers in the establishment of linguistic human rights. Particular reference is made to the language continua found in Scotland and African America which currently lack their own distinct dictionaries. In Scotland, various attempts to codify the opposite extremes of the spectra (typically identified as 'Scottish Standard English' and 'Scots' respectively), while useful for classifying individual lexical items, run the risk of simultaneously obscuring the picture of actual usage. Lexicographers constantly enter into the debate about language and identity in their codification of words as the building-blocks of culture, and play a role in the perception of language varieties and their relative prestige. From an examination of lexicographical method, and of past and present attitudes to dictionaries, we can observe models of 'best practice' that facilitate more positive perceptions of language.